THE EFFECT OF MERGER ANNOUNCEMENTS ON ABNORMAL RETURNS AND STOCK TRADING VOLUME ACTIVITIES (STUDY ON BANKING COMPANIES IN BANK INDONESIA) - Wairooy, Mohamad Ali (Perpustakaan dan Penerbitan Unismuh Makassar, 2018)
The purpose of this study is to find out the price and trading volume activity of shares in the Jakarta Stock Exchange on the event of merger announcements, also to find out whether there are differences in average abnormal returns and the activity of stock trading volume between before and after the announcement of the merger. The stock samples chosen in this study are stocks that are included in the banking sector and LQ- 45 index with the consideration that these stocks are stocks that can represent the population of the banking sector in terms of the number of shares traded and the market capitalization value . To test the information content of the event, the event study method is used. The test results show that the Jakarta Stock Exchange did not react to the event of the merger announcement. This can be seen from the absence of test results that provide a minimum level of significance of the set that is 95%. The difference in the average abnormal return at the time of the announcement and around the announcement was also not proven significantly. Meanwhile, the difference in average trading volume activity at the time of the announcement and around the announcement actually shows the opposite, which is proven significantly at the 99% confidence level.